Associations Between Parental Employment and Children's Screen Time: A Longitudinal Study of China Health and Nutrition Survey - Qian-Wen Xie; Qian-Wen Xie; Qian-Wen Xie; Qian-Wen Xie; Xiangyan Luo; Roujia Chen; Xudong Zhou; Xudong Zhou (Frontiers Media S.A., 2023)
Objectives: Parents are often torn between their parenting roles in the family and working roles at the workplace. This study focused on the associations of parental employment with children's screen time (ST) on weekdays, weekends, and during the entire week.Methods: Unbalanced panel data including 2,977 children (aged 0-17 years) from five waves of the China Health and Nutrition Survey data from 2004 to 2015 were utilized. Two-way fixed effects models were fitted to examine the associations of parental employment status, working hours, and overwork with children's ST.Results: Compared to unemployment status, maternal formal employment positively predicted children's ST on both weekdays and weekends, while maternal informal employment was associated with increased children's ST on weekends. The more hours they worked, the more time their children spent using screens. Neither employment status nor the overwork of fathers was significant.Conclusion: Parental employment, especially maternal employment, was linked with the ST of children. More childcare-friendly labor policies are needed to promote healthy lifestyles among the next generation.